Анализ и оценка факторов, влияющих на изменение уровня оплаты труда - Смоловик, Раиса Федоровна; Берко, И. Ю. (НТУ "ХПИ", 2010)
In the article the problems of payment of labour are analysed in Ukraine, taking into account the modern terms of crisis situation; factors, influencing on the change of level of payment of labour; the comparative analysis of payment of labour is given on the economic developed countries.
Keywords: заработная плата; сила рабочая; продуктивность; уровень жизни населения